Phenotypic Plasticity or a Reproductive Dead End? Primnoa pacifica (Cnidaria: Alcyonacea) in the Southeastern Alaska Region - Waller, Rhian G.; Stone, Robert P.; Rice, Lauren N.; Johnstone, Julia; Rossin, Ashley M.; Hartill, Elise; Feehan, Keri; Morrison, Cheryl L. (Frontiers in Marine Science, 2019)
Red tree corals (Primnoa pacifica) are abundant in the eastern Gulf of Alaska, from the glacial fjords of Southeast Alaska where they emerge to as shallow as 6 m, to the continental shelf edge and seamounts where they are more commonly found at depths greater than 150 m. This keystone species forms large thickets, creating habitat for many associated species, including economically valuable fishes and crabs, and so are important benthic suspension feeders in this region. Though the reproductive periodicity over 1.5 year period was reported in 2014 from a shallow fjord (Tracy Arm), this study examined reproductive ecologies from 8 sites – two within Glacier Bay National Park and Preserve, three on the continental shelf edge, one within Endicott Arm (Holkham Bay) and two time points from the Tracy Arm (Holkham Bay) study. Male reproductive traits were similar at all sites but there were distinct differences in oogenesis. Though fecundity mostly showed no significant difference between sites, there was a trend of increasing number of eggs with depth. Indeed, the average oocyte sizes from Tracy Arm (the shallowest site) was 105 m, whereas from Shutter Ridge (one of the deepest sites) the average size was 309 m. Moreover, the maximum oocyte size at Tracy Arm was 802 m, whereas it was 2120 m at Dixon Entrance, an almost 3-fold difference, and one not usually observed within a single species. We propose two theories to explain the observed differences, a) this species shows great phenotypic plasticity in reproductive ecology, adjusting to different environmental variables based on energetic need and potentially demonstrating micro-evolution; or b) the fjord sites are at a reproductive dead end, with the stress of shallow water conditions effectively preventing gametogenesis reaching full potential and likely limiting successful reproductive events from occurring, at least on a regular basis.